Morphometric analysis of scaphoid: influence of screw design and surgical approach in scaphoid fracture fixation: a study in Indian population - Yadav, Saurabh; Jena, Saikat; Verma, Tarun (International Journal of Research in Orthopaedics, 2025)
Scaphoid fractures are among the most frequent carpal bone injuries, and screw fixation has become the treatment of choice. The stability of fixation is maximized when the screw is centrally placed and of maximum possible length. In this case series, we examined scaphoid morphometry in the Indian population and assessed the influence of sex, surgical approach, and screw design on achievable screw length. The study was performed on ten computed tomography (CT) scans of normal wrists, including five men and five women. Three-dimensional reconstructions were created, and the central longitudinal axis of the scaphoid was defined. Virtual headless compression screws from five commercially available designs were positioned along this axis. The scaphoid length measured along its central axis was greater in men (mean 27.52 mm, standard error of the mean 0.70 mm) than in women (mean 23.32 mm, standard error of the mean 0.61 mm). Longer screws could be inserted through a volar approach (male mean 25.28 mm, standard error of the mean 0.84 mm; female mean 20.92 mm, standard error of the mean 0.91 mm) compared with a dorsal approach (male mean 24.84 mm, standard error of the mean 0.94 mm; female mean 20.48 mm, standard error of the mean 1.00 mm), irrespective of screw design. This case series highlights sex-related differences in scaphoid size and suggests that the volar approach permits the placement of longer screws. Screw design continues to play a crucial role in determining fixation options.